2009
DOI: 10.1111/j.1538-7836.2009.03384.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of venous thromboembolism: a key patient safety priority

Abstract: Summary. It is more than 50 years since the first publication of a study showing that symptomatic and fatal venous thromboembolism could be reduced with the use of thromboprophylaxis. Furthermore, it is 23 years since the first evidence-based guidelines recommended routine use of thromboprophylaxis for most hospitalized patients. However, despite the overwhelming evidence that thromboprophylaxis safely and inexpensively reduces thromboembolic complications associated with acute illness and surgery, there conti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 70 publications
0
43
0
4
Order By: Relevance
“…5,37 Almost 60% of VTE events in western communities are potentially preventable because they are provoked by surgery or a medical illness and develop during or soon after admission to hospital. 2,15 The key to reducing the morbidity and mortality of VTE is effective prophylaxis, because death from embolism is often rapid and most large emboli discovered at autopsy were clinically unsuspected during life.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5,37 Almost 60% of VTE events in western communities are potentially preventable because they are provoked by surgery or a medical illness and develop during or soon after admission to hospital. 2,15 The key to reducing the morbidity and mortality of VTE is effective prophylaxis, because death from embolism is often rapid and most large emboli discovered at autopsy were clinically unsuspected during life.…”
Section: Discussionmentioning
confidence: 99%
“…3 These statistics make VTE a major patient safety issue for hospitals. [5][6][7] As prophylaxis is known to reduce the rate of VTE, [8][9][10] the National Institute of Clinical Studies, an institute of the National Health and Medical Research Council (NHMRC), identified the need to address the underuse of preventive measures for VTE in Australian hospitals as a clinical priority. 11 This paper presents the latest recommendations contained within the NHMRC's Clinical Practice Guideline for the prevention of VTE in patients admitted to Australian hospitals, as one part of the strategy to increase appropriate VTE prophylaxis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a systematic review of the pediatric literature has demonstrated that at least 20% of children with limb DVT develop post-thrombotic syndrome (PTS), a syndrome of chronic venous insufficiency often associated with limitation in age-appropriate physical activities that are critical to normal growth and development. 7 Recommendations for prevention of hospital-acquired VTE in adults are well established 8 and have been informed by evidence from randomized controlled clinical trials. In pediatrics, such recommendations and data are largely lacking, historically attributable to the rarity of VTE in this population.…”
Section: Introductionmentioning
confidence: 99%
“…Thromboembolism prophylaxis has been identified as an algorism of primary importance to improve patient safety in practice 12. However, there is still considerable underutilization of appropriate pharmacologic or mechanical prophylaxis across a broad range of patients with known DVT risk 1314…”
Section: Introductionmentioning
confidence: 99%